Isolating Peer Effects in the Returns to College Selectivity (2019)
This paper asks how a student¿s classmates affect her returns to college. We exploit a ¿tracking¿ admission system at a selective Colombian university that led to large differences in mean classmate ability for students in the same programs. In a regression discontinuity design, we find that students in higher-ability classes were more likely to fail courses and drop out, and had lower earnings one decade later. Testable predictions from a human capital model with peer externalities show that individuals learned less in more able classrooms. Our findings suggest that exposure to higher-ability college peers can harm an individual¿s career trajectory.